Comparison of spray drying, freeze drying and convective hot air drying for the production of a probiotic orange powder. (August 2015) - Barbosa, J.; Borges, S.; Amorim, M.; Pereira, M.J.; Oliveira, A.; Pintado, M.E.; Teixeira, P.
Highlights: Probiotic orange powders were obtained by spray-, freeze- and hot air drying techniques. During drying, cell inactivation was only observed for convective hot air dried cells. Reductions of P. acidilactici HA-6111-2 were minimal at most conditions of storage. Minimal reductions of L. plantarum 299v were observed during storage at 4 °C. Better dissolution, colour and vitamin C retention were obtained by freeze- or spray-drying. Abstract: Survival of two LAB in orange powders obtained by spray-(SD), freeze-(FD) and convective hot air drying (CD) was investigated during drying and subsequent storage. Colour and vitamin C content of the powders were also evaluated. There was no decrease in the cell number during SD and FD, but a reduction of 2 log cycles was obtained in CD. During storage at 4 °C no significant differences ( p > 0.05) in the survival of Lactobacillus plantarum 299v were observed for the orange powder obtained by the different techniques. However, during storage at room temperature, its survival was better in orange powders prepared by CD. For Pediococcus acidilactici HA-6111-2, reductions during storage were minimal for most of the conditions investigated. Considering the initial cell number obtained after each drying process, SD and FD allowed survival of an increased number of cells after storage period. The best colour retention was obtained by FD, with no maltodextrin, and the higher total vitamin C retention was achieved in SD and FD powders. By the high production costs and long drying times of FD, it can be concluded that SD could be a good method to produce a new functional non-dairy product, such as a probiotic orange juice powder.